2022
DOI: 10.1002/jcb.30309
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of statins on osteoarthritis: A review

Abstract: Osteoarthritis (OA) is a progressive joint disease. The etiology of OA is considered to be multifactorial. Currently, there is no definitive treatment for OA, and the existing treatments are not very effective. Hypercholesterolemia is considered a novel risk factor for the development of OA. Statins act as a competitive inhibitor of the β‐hydroxy β‐methylglutaryl‐CoA (HMG‐CoA) reductase and are widely used to manage hypercholesterolemia. Inhibition of HMG‐CoA reductase results in reduced synthesis of a metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 104 publications
(205 reference statements)
0
3
0
Order By: Relevance
“…Our study further supports the positive effects of statins in preventing OA. In particular, atorvastatin has been shown to protect against cartilage degeneration following IL-1β stimulation and elicit anti-inflammatory effects through the stimulation of the STAT1-caspase-3 signaling pathway [ 32 ]. Studies by Pathak et al demonstrated that atorvastatin can reduce the inflammatory response induced by monosodium iodoacetate in a rat joint model [ 8 ].In their study, Jiancongchen et al found that atorvastatin could suppress matrix degradation in rat nucleus pulposus cells induced by TNF-α [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study further supports the positive effects of statins in preventing OA. In particular, atorvastatin has been shown to protect against cartilage degeneration following IL-1β stimulation and elicit anti-inflammatory effects through the stimulation of the STAT1-caspase-3 signaling pathway [ 32 ]. Studies by Pathak et al demonstrated that atorvastatin can reduce the inflammatory response induced by monosodium iodoacetate in a rat joint model [ 8 ].In their study, Jiancongchen et al found that atorvastatin could suppress matrix degradation in rat nucleus pulposus cells induced by TNF-α [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statins are commonly used to lower cholesterol levels by inhibiting 3-hydroxy-3methylglutaryl-CoA. However, they also have anti-in ammatory and antioxidant properties, which may bene t cartilage repair and regeneration 23,26,27 . This mechanism is bene cial in preventing cartilage degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, drug repositioning-also known as drug repurposing, repro ling, rescue, redirecting, switching, or retaking-has emerged as a promising strategy for developing new treatments for various diseases, including osteoarthritis [14][15][16][17][18][19][20][21][22][23] . Drug repositioning involves the identi cation of existing or abandoned drugs that may have therapeutic potential for new indications 24 .…”
Section: Introductionmentioning
confidence: 99%
“…More interestingly, the presence of sOA correlated with lower serum lipids, which could be explained with the influence of statin therapy, but also due to the high membrane uptake of cholesterol caused by an increased cell turnover in the bone marrow, potentially suggesting a more aggressive disease biology in MPN patients with OA [ 68 , 69 ]. Considering that statins may exert beneficial effects on both the osteoarticular system [ 70 ] and the MPN clone [ 71 , 72 ], additional studies are needed to unravel whether these compounds may also potentially have beneficial effects on OA development and progression in MPN patients.…”
Section: Discussionmentioning
confidence: 99%